MODEL INFORMASI KEPUTUSAN BERBASIS TOPSIS APLIKASI ANDROID - Taufiq; Maryana; M.Daud (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Information Technology in spatial data processing has developed to a point where these results are in line with the application challenges required by natural resource management. In addition, the internet, geomatics, and telecommunications are rapidly changing the way natural resources are managed and protected. These provide more accurate and up-to-date information and are quickly available to users. Regional potential is a product that exists in an area that can be developed and is able to provide benefits to the local community and can be used as a supporter of the national economy. This understanding gives the connotation that optimal management planning is needed in order to achieve the intended expectations, so this decision support system is presented in a simple form for easy access on Android smartphone devices. Applications are made with Eclipse as an editor as well as compile and builder and SQLite for the application database.